Boosting hot electron flux and catalytic activity at metal–oxide interfaces of PtCo bimetallic nanoparticles - Hyosun Lee (Nature Portfolio, 2018)
The real-time quantitative detection of hot electrons provides critical clues to understand the origin of the enhanced catalytic performance of bimetallic nanoparticles (NPs). Here, the authors investigate hot electrons generated on bimetallic PtCo NPs during H2 oxidation by measuring the chemicurrent on a catalytic nanodiode.